Job crafting and organizational support base on cooperative employee performance with work engagement mediation - Pratiwi, Hasna Widya (Enrichment : Journal of Management, 2025)
This study started from the decline in performance shown by employees of one of the leading cooperatives in Kendal Regency. At the beginning of this year, they could not complete the marketing target which is basically easy for employees to complete. This study will discuss how employee performance is based on job crafting and organizational support with work engagement mediation. The results of this study are expected to be input for cooperative companies that are currently developing, especially in terms of human resources. This study has an explanatory research basis using a census technique which means using the population as a sample of this study which amounted to 57 respondents. The test in this study used the Smart-PLS application. This study shows that organizational support and work engagement have a positive and significant effect on employee performance, while job crafting does not affect employee performance. In this study, organizational support also has a positive and significant effect on work engagement, while job crafting does not affect work engagement. While the mediation effect of work engagement only affects the results of organizational support on employee performance, while the results of job crafting on employee performance have no effect